The Effectiveness of Digital Comic Modification of Golden Cucumber Folklore on Breast Cancer Prevention Behavior with Herbal Plants in Gen Z: Efektivitas Komik Digital Modifikasi Folklore Timun Emas Terhadap Perilaku Pencegahan Kanker Payudara Dengan Tanaman Herbal Pada Gen Z - Restu Ayu Eka Pustika Dewi; Lestari, Catur Retno; Kusuma, Daffa (Jurnal Ilmiah Kesehatan, 2025)
Breast cancer has a high incidence rate, particularly among women. Early prevention efforts are essential, especially through educational media that appeal to Generation Z. This study aims to analyze the effectiveness of a modified folklore timun emas digital comic on breast cancer prevention behavior using herbal plants in generation z. the research employed a pre-experimental one-group pretest-posttest design, conducted in RW 02 Lamper Krajan, Lamper Lor Village, South Semarang District. The study population consisted of all Generation Z individuals in the area, totaling 87 people. The sample was selected using a purposive sampling technique, resulting in 79 respondents. The Wilcoxon test results showed a p-value of 0.001, indicating a significant effect of the modified folklore Timun Emas digital comic on breast cancer prevention behavior using herbal plants. Future studies are recommended to develop digital comics with interactive features and more engaging visuals to enhance reader involvement. Keywords : Breast Cancer, Gen Z , Herbal Plant, Digital Comic